METHANE PRODUCTION FROM CASSAVA STARCH WASTEWATER IN PACKED-BED REACTOR AND CONTINUOUS FLOW - Araujo,Izabela R. C. (2018)
ABSTRACT The aim of this study was to evaluate the behavior of an anaerobic reactor of packed-bed and continuous flow, in relation to the biogas and methane production and the removal of organic load, from the wastewater of cassava starch extraction. For this purpose, were tested, in a reactor with a useful volume of 2.82 L and support mean of polypropylene filled with polyethylene foam, the organic loading rate (OLR) of 2.5, 5.0, 8.0 and 10.0 g L-1d-1. It was evaluated the removal of COD, the pH, the VA/TA ratio, the biogas and the methane production. It was concluded from this study that it is possible to produce biogas with methane percentages higher than 80% (maximum) and remove the organic load more than 90% under the tested conditions. In relation to stability, the reactor can be considered stable for the parameters, pH, the relationship between volatile acidity and total alkalinity and organic load removal. The best results in relation to the average volumetric biogas production (0.174 and 0.311 L g COD-1) were obtained for the higher organic loading rate (of 8 and 10 g L-1d-1, respectively) and the observed tendency is that with the increase of the organic loading rate, the specific biogas production will increase as well as the specific production of methane.